2022
DOI: 10.3847/1538-4357/ac8471
|View full text |Cite
|
Sign up to set email alerts
|

CLEAR: The Evolution of Spatially Resolved Star Formation in Galaxies between 0.5 ≲ z ≲ 1.7 Using Hα Emission Line Maps

Abstract: Using spatially resolved Hα emission line maps of star-forming galaxies, we study the spatial distribution of star formation over a wide range in redshift (0.5 ≲ z ≲ 1.7). Our z ∼ 0.5 measurements come from deep Hubble Space Telescope (HST) Wide Field Camera 3 G102 grism spectroscopy obtained as part of the CANDELS Lyα Emission at Reionization Experiment. For star-forming galaxies with log(M */M ⊙) ≥ 8.96, the mean Hα effective radius is 1.2 ± 0.1 times larger than that of the stellar continuum, implying insid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 161 publications
7
26
0
Order By: Relevance
“…4). Matharu et al (2022) found that size measurements in CANDELS-like HST imaging are less reliable for galaxies at these redshifts with M * 10 9 M (primarily this is because the sizes of the galaxies are small and approaching the resolution limit of the HST WFC3 image.). We therefore apply this mass limit to our study here.…”
Section: Sample Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…4). Matharu et al (2022) found that size measurements in CANDELS-like HST imaging are less reliable for galaxies at these redshifts with M * 10 9 M (primarily this is because the sizes of the galaxies are small and approaching the resolution limit of the HST WFC3 image.). We therefore apply this mass limit to our study here.…”
Section: Sample Selectionmentioning
confidence: 99%
“…We use galfit (Peng et al 2002(Peng et al , 2010 for the morphology measurements following the two-galfit-run approach from Matharu et al (2019Matharu et al ( , 2022, which leads to a high level of agreement with published size measurements (see more details in Matharu et al 2019). For each galaxy, we create 10 × 10 cutouts of NUV-, PAHbands and F160W and associated error images, centered on its F160W coordinates.…”
Section: The Morphology Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CLEAR spectra have been used to study the metallicities, ages, and formation histories of massive high-redshift galaxies (Estrada-Carpenter et al 2019Simons et al 2021) and appraise Paschen-β as an SFR indicator in low-redshift galaxies (Cleri et al 2022). Matharu et al (2022) used spatially resolved Hα emission-line maps of star-forming galaxies to study the evolution of gradients in galaxy assembly. Jung et al (2022) used CLEAR to study the evolution of the strength of Lyα emission at 6.5 < z < 8.2.…”
Section: Observations and Data Reductionmentioning
confidence: 99%
“…Spatially resolving Hα gives the profile of star formation within a galaxy. This gives us information about whether a galaxy is formed inside-out or outside-in by comparing to the galaxy's stellar continuum (Nelson et al 2012(Nelson et al , 2016a(Nelson et al , 2021Matharu et al 2022). Spatially resolving the Balmer decrement (Hα/Hβ) measures the profile of dust attenuation within a galaxy.…”
Section: Introductionmentioning
confidence: 99%